Effectiveness Management of Qualitative Research in Writing Scientific Papers - Royadi, Dedi; Susiana, Nancy; Khumaida, Fina Andhara (Pandawan, 2019)
Good scientific work must have data that is not surprising or real facts. In managing this work, significant research methods are needed. However, some management uses in research are still not maximal and do not know the limitations of qualitative research. For example, are there researchers who do not yet know clearly what forms of management will be qualitative. Qualitative forms are often referred to as in accordance with quality. In this study will discuss the management of qualitative, qualitative, qualitative, and qualitative research. The existence of this study is expected to be used in research as well as using qualitative research procedures. Keywords: management, qualitative research, perspective.